2016
DOI: 10.1007/s11661-016-3499-2
|View full text |Cite
|
Sign up to set email alerts
|

The Strength–Grain Size Relationship in Ultrafine-Grained Metals

Abstract: Metals processed by severe plastic deformation [SPD] techniques, such as equal-channel angular pressing [ECAP] and high-pressure torsion [HPT], generally have submicrometer grain sizes. Consequently, they exhibit high strength as expected on the basis of the HallPetch [H-P] relationship. Examples of this behavior are discussed using data on Ti, Al-Mg 1 and Ni. These materials typically have grain size above ~50 nm where softening is not expected. An increase in strength is usually accompanied by a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 150 publications
1
38
0
Order By: Relevance
“…Figure reveals that deformed specimens show little or no discontinuous yielding region after heat treatment. It is expected that in the higher amounts of deformation, serrated region would return to stress − strain curves, as it can slightly be seen in 3‐passes CGPed samples heat treated at 700, 950, and 1050 °C. Note that samples annealed at 850 °C and subsequently water‐quenched represented rather different behavior due to their unique microstructure which will be discussed later.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure reveals that deformed specimens show little or no discontinuous yielding region after heat treatment. It is expected that in the higher amounts of deformation, serrated region would return to stress − strain curves, as it can slightly be seen in 3‐passes CGPed samples heat treated at 700, 950, and 1050 °C. Note that samples annealed at 850 °C and subsequently water‐quenched represented rather different behavior due to their unique microstructure which will be discussed later.…”
Section: Resultsmentioning
confidence: 94%
“…These disadvantages are undesirable for structural applications, for example, steel specifications include upper limits to yield ratio varying between 0.70 and 0.93 in several industrial aspects . In this regards, several experiments have been conducted on post‐annealing of severely plastic deformed materials in order to reduce their dislocation density and improve the ductility in combination with their thermal stability . It is shown that although materials can regain their formability through annealing process, this is often accompanied by reduction in the strength, and sometimes a slight increase in strength is obtained .…”
Section: Introductionmentioning
confidence: 99%
“…(1) Grain refinement. According to the Hall-Patch equation, the yield stress of metals increases with finer grain size [15]. For the Ti-6Al-4V alloys, the mechanical strength increases with a reduction in grain size [16].…”
Section: Discussionmentioning
confidence: 99%
“…ODF sections at 4 2 ¼ 45 obtained from EBSD measurements of Fe-36%Ni (wt.%) alloy after HPT processing for 1/2 to 10 turns at ambient temperature and 250 C, respectively. HallePetch relationship for ultrafine-grained (100e1000 nm) materials produced by SPD processing [43,44]. In nanostructured alloys below~10 nm an inverse Hall-Petch relationship may occur due mainly to the operation of grain boundary sliding [45] but a deviation from the HallePetch relationship was also reported at grain sizes smaller than~500 nm in an AleMgeSi alloy processed by HPT at room temperature [25] and this was explained by the easy movement of extrinsic dislocations in the non-equilibrium grain boundaries introduced by HPT processing.…”
Section: Microhardeness Evolution After Hpt Processingmentioning
confidence: 99%